Albania : Recent Economic Developments and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews macroeconomic developments in Albania during 1997-99. Backed by a tightening of monetary policy, inflation subsided quickly in the second half of 1997, and the exchange rate recovered from its earlier sharp depreciation. In 1998, the authorities continued on the path toward macroeconomic stabilization, implementing a tight budget with savings in noninterest current spending and strong revenue measures. Inflation decreased rapidly from 42 percent at end-1997 to below 9 percent at end-1998 and continued on its downward path in 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet